Nature, age and emplacement of the Spongtang ophiolite, Ladakh, NW India - Catlos, Elizabeth J.; Schwarz, Winfried H.; Schmitt, Axel Karl (Journal of the Geological Society, 2019)
Skip to Next Section - The Spongtang ophiolite (Ladakh, NW India) constrains the nature of oceanic lithosphere before Indo-Asia collision and key stages in the development of the Himalayas. We report whole-rock 40Ar/39Ar and in situ zircon 238U-206Pb ages from its crustal and upper and lower mantle sequences. Major and trace elements from harzburgite minerals suggest that the ophiolite formed at a mid-ocean ridge-type spreading centre, whereas published spinel compositions from Spongtang dunites are consistent with a suprasubduction-zone setting. Rare earth element-in-two-pyroxene thermometry for the harzburgite yields 1058 ± 13°C whereas temperature from solvus-based two-pyroxene and olivine-spinel thermometry is lower (to 656°C). The distribution suggests that the mantle section of the ophiolite cooled at rates of 100° Ma−1 or slower. Based on ages, major and trace element geochemistry, and geospeedometric estimates, we model the origin of the Spongtang ophiolite as forming within a mid-ocean ridge-type spreading centre with a spreading rate >2 cm a−1 in the Neotethyan Ocean, possibly from the Late Triassic to Jurassic. By the Early Cretaceous, the ridge experienced increasing influence of subduction beneath the Spongtang oceanic lithosphere owing to a subduction polarity reversal. Based on 238U-206Pb ages of the youngest Cenozoic zircon grain, latest obduction occurred between 64.3 ± 0.8 and 42.4 ± 0.5 Ma, in accordance with 56.7 ± 5.2 Ma whole-rock 40Ar/39Ar ages. - Supplementary material: Excel files with details of electron microprobe and inductively coupled plasma mass spectrometry (ICP-MS) analyses, argon isotopic whole-rock and secondary ion mass spectrometry (SIMS) analyses, and the TREE calculations, including an inversion diagram showing regression through measured REE distributions in cpx and opx (from Liang et al. 2013), are available at https://doi.org/10.6084/m9.figshare.c.4261856